Estudo da viabilidade técnica para obtenção de superfície duplex em aço inoxidável martensítico AISI 410 através do processo de deposição a plasma por gaiola catódica - Santos, Poliana Rochele Félix dos (2013)
The technique of plasma nitriding by the cathode cage mainly stands out for its ability to produce uniform layers, even on parts with complex geometries. In this study, it was investigated the efficiency of this technique for obtaining duplex surface, when used, simultaneously, to nitriding treatment and thin film deposition at temperatures below 500°C. For this, were used samples of AISI 41 0 Martensitic Stainless Steel and performed plasma treatment, combining nitriding and deposition of thin films of Ti and/or TiN in a plasma atmosphere containing N2-H2. It was used a cathodic cage of titanium pure grade II, cylindrical with 70 mm diameter and 34 mm height. Samples were treated at temperature 420ºC for 2 and 12 hours in different working pressures. Optical Microscopy (OM), Scanning Electron Microscopy (SEM) with micro-analysis by Energy Dispersive Spectroscopy (EDS), X-Ray Diffraction (XRD), Atomic Force Microscopy (AFM) and analysis of Vickers Microhardness were used to investigate coating properties such as homogeneity and surface topography, chemical composition, layer thickness, crystalline phase, roughness and surface microhardness. The results showed there is a direct proportionality between the presence of H2 in plasma atmosphere and the quantity of titanium in surface chemical composition. It was also observed that the plasma treatment at lowpressure is more effective in formation of TiN thin film